The other way around?

g(x) = (x -10)(2 -x)

g(x) = 2x -x^2 -20 +10x

g(x) = -x^2 +12x -20

It should be the same direction now.

The zeros are of course x = 10 and x = 2.

Axis of symmetry:

g(x) = -x^2 +12x -20

At vertex, x = -b/2a

x = -12/(2(-1)) = 6

So, the axis of symmetry is x = 6

The coordinates of the vertex:

g(6) = -(6^2) +12(6) -20 = 16

So, (6,16) ------the vertex.

-----------------------------------------

The rest should be the same in rearranging them from "the other around".